Культура Окінави в Японії - Масімо Ацусі (Народна творчість та етнографія, 2009)
The separate financial and spiritual questions of culture of island Okinawa, which is situated in the south-west part of the Japanese archipelago, are examined in the article. Religious beliefs, peculiarities of feeding, house building and musical harmony, and many other things are covered.